2011
DOI: 10.1063/1.3665405
|View full text |Cite
|
Sign up to set email alerts
|

A transfer technique for high mobility graphene devices on commercially available hexagonal boron nitride

Abstract: We present electronic transport measurements of single-and bilayer graphene on commercially available hexagonal boron nitride. We extract mobilities as high as 125 000 cm 2 V −1 s −1 at room temperature and 275 000 cm 2 V −1 s −1 at 4.2 K. The excellent quality is supported by the early development of the ν = 1 quantum Hall plateau at a magnetic field of 5 T and temperature of 4.2 K. We also present a new and accurate transfer technique of graphene to hexagonal boron nitride crystals. This technique is simple,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
309
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(314 citation statements)
references
References 14 publications
5
309
0
Order By: Relevance
“…For example, samples with the commonly used SiO 2 substrate replaced by hexagonal boron nitride (h-BN) which has a lattice constant very close to that of graphene and an almost atomically flat surface with strongly reduced disorder, 12,13 have shown highly improved transport characteristics with mobilities approaching that of suspended graphene. 8,14,15 Furthermore, the high energy of the surface-optical phonons of h-BN results in a significant reduction of surface-optical phonon scattering [16][17][18] that for commonly used gate oxides starts to dominate the mobility around T ∼ 150-200 K. 5,7 When the mobility is dominated by acoustic phonon scattering, two transport regimes separated by the Bloch-Grüneisen (BG) temperature T BG = 2hk F c ph /k B can be identified. 19 Here, k F is the Fermi wave vector, c ph the sound velocity, and k B the Boltzmann constant (T BG ∼ 57 K √ n for the longitudinal acoustic phonon with the two-dimensional carrier density n measured in units of 10 12 cm −2 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, samples with the commonly used SiO 2 substrate replaced by hexagonal boron nitride (h-BN) which has a lattice constant very close to that of graphene and an almost atomically flat surface with strongly reduced disorder, 12,13 have shown highly improved transport characteristics with mobilities approaching that of suspended graphene. 8,14,15 Furthermore, the high energy of the surface-optical phonons of h-BN results in a significant reduction of surface-optical phonon scattering [16][17][18] that for commonly used gate oxides starts to dominate the mobility around T ∼ 150-200 K. 5,7 When the mobility is dominated by acoustic phonon scattering, two transport regimes separated by the Bloch-Grüneisen (BG) temperature T BG = 2hk F c ph /k B can be identified. 19 Here, k F is the Fermi wave vector, c ph the sound velocity, and k B the Boltzmann constant (T BG ∼ 57 K √ n for the longitudinal acoustic phonon with the two-dimensional carrier density n measured in units of 10 12 cm −2 ).…”
Section: Introductionmentioning
confidence: 99%
“…8,17 For charge transport, it has been shown that the carrier mobility of graphene devices on SiO 2 is mainly limited by interfacial charged impurities, surface roughness, and phonons. [18][19][20] The demonstration of an order-of-magnitude improvement in the mobility of graphene encapsulated between atomically flat, charge trap free boron nitride crystals 21,22 has triggered the recent spin transport studies in encapsulated single layer and recently bilayer graphene-based spin valves, where a spin-relaxation length of up to~12 μm and~24 μm have been observed, respectively. 23,24 For the case of bilayer graphene, the initial experiments on SiO 2 revealed an inverse scaling between spin and momentum relaxation times, for example, the longest spinrelaxation times were observed in the lowest-mobility devices.…”
Section: Introductionmentioning
confidence: 99%
“…8,17 For charge transport, it has been shown that the carrier mobility of graphene devices on SiO 2 is mainly limited by interfacial charged impurities, surface roughness, and phonons. [18][19][20] The demonstration of an order-of-magnitude improvement in the mobility of graphene encapsulated between atomically flat, charge trap free boron nitride crystals 21,22 has triggered the recent spin transport studies in …”
mentioning
confidence: 99%
“…The results of our investigation on the mechanisms of MIT and other intrinsic characteristics, such as thickness-dependent screening abilities and fast relaxation of hole carriers at the valence band, provide useful information much needed for improving the performance of the FET devices based on MoS 2 monolayers and multilayers. Figure 1a,b illustrates our specially designed MIS-M capacitor device, fabricated by transferring 23,36 exfoliated flakes of MoS 2 and hexagonal boron nitride (BN) on a Si substrate coated with a SiO 2 thin layer (300 nm). Exfoliated natural crystals of monolayer or multilayer MoS 2 were first transferred onto a BN sheet, serving as an ultra-smooth and disorder-free gate dielectric 37 .…”
mentioning
confidence: 99%